Effects of Learning Management Through the Challenges of Elderly Care in the 21st Century on Promoting Self-directed Learning and Knowledge Development in Nursing Students - Daemayu, Amanee (Princess of Naradhiwas University Journal, 2025)
Background and Objectives The number of elderly population structures is continuously increasing in the 21st century, leading to challenges in providing complex care for the elderly, including illness, dependency, mental health issues, social, economic, technological, and other factors that impact the nursing profession in the current era. Learning management through challenging issues is learning through real-life situations and problems, providing opportunities independently through self-directed learning with learning behaviors, management skills, self-information retrieval, and assessment, which are then used for debate discussion on the chosen topic reasonably. This approach fosters analytical thinking, professional skills, and systematic problem-solving, as well as lifelong learning. This research is a single-group quasi-experimental study with pre- and post-test measurements. Its objectives were to compare the promotion of self-directed learning among nursing students before and after learning management through challenging issues in elderly care in the 21st century and to compare nursing students’ knowledge scores before and after learning management through challenging issues in elderly care in the 21st century. Methods The sample group consisted of 30 nursing students enrolled in the Geriatric nursing course in the second semester of the 2024 academic year. The research instruments used were lesson plans, teaching materials, case studies, and a debate on the challenges of caring for the elderly in the 21st century. The content validity index (CVI) was 0.92. The data collection instruments were a general information questionnaire, a self-directed learning promotion questionnaire for nursing students, and a nursing student knowledge test. The content validity indexes (CVI) for these instruments were 1, 0.97, and 0.97, respectively. The reliability of the self-directed learning promotion questionnaire for nursing students was tested, yielding a Cronbach’s alpha coefficient of 0.95. The knowledge test for nursing students had a KR-20 value of 0.86. Data were analyzed using descriptive statistics and paired t-tests, as per the initial agreement. Results 1) Self-directed learning promotion among Nursing students after participating in learning management through the challenges of elderly care in the 21st century statistically significantly increased both overall and in each aspect (p < .05). 2) The average knowledge score of nursing students statistically significantly increased from 53.37 to 55.97 (p < .05) after learning management through the challenges of caring for the elderly in the 21st century (p < .01). Conclusion and Recommendation Learning management through the challenges of elderly care in the 21st century helps promote self-directed learning. The increasing knowledge scores of nursing students indicate that learners develop critical thinking skills, self-management, information retrieval, and self-assessment skills. Therefore, promoting self-directed learning should be applied in nursing education in complex elderly care situations.